2012
DOI: 10.5005/jp-journals-10026-1041
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Histopathological Patterns of Oral Squamous Cell Carcinoma at a Tertiary Level Referral Hospital in Hyderabad, India: A 5-Year Retrospective Study

Abstract: Background: To study the demographics and histopathological patterns of oral squamous cell carcinoma (OSCC) reported at a tertiary level referral teaching hospital in Hyderabad, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The prevalence of OSCC patients was significantly higher in middle age groups (41-50 and 51-60 years) in our study. Some recent studies of India (Saraswathi et al, 2006;Kiran et al, 2012) have reported that majority of the OSCC patients were in the age group of 41 to 50 years and 40 to 61 years respectively. However, (Gangane et al, 2007) reported prevalence of oral malignancies mostly in the 50 to 59 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSCC patients was significantly higher in middle age groups (41-50 and 51-60 years) in our study. Some recent studies of India (Saraswathi et al, 2006;Kiran et al, 2012) have reported that majority of the OSCC patients were in the age group of 41 to 50 years and 40 to 61 years respectively. However, (Gangane et al, 2007) reported prevalence of oral malignancies mostly in the 50 to 59 years age group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients were in the 5th and 6th decade (40-60yrs) which is consistent with Singh, Sharma, Krishna, Kiran et al and Saraswati et al, Sankaranarayan et al found that the peak-age of occurrence which is fifth decade in India is at least a decade earlier than that described in the western literature. [19][20][21][22][23][24] Gupta et al observed an increase in the incidence of oral cancer in the younger (less than 50 years) age group. 25 Epidemiological study of oral cancer in India by Chattopadhyay et al and Mathew et al reported that in developing countries, oral cancer may affect younger men and women more frequently than seen in the western world.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, dentists play a pivotal role in educating the public, diagnosis and long-term follow-up of patients at risk and to avoid local recurrence and lymph node metastases. [ 8 9 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first study looking into the districts and population of Bidar and Gulbarga of North Karnataka. [ 8 9 10 ] This pilot study was conducted to determine the epidemiological profile and clinical characteristics of OPMD and OC among the population of Bidar and Gulbarga districts of North Karnataka, India.…”
Section: Introductionmentioning
confidence: 99%